Multi-Omics Characterizes the Effects and Mechanisms of CD1d in Nonalcoholic Fatty Liver Disease Development - Zheng, Qiuxian; Xue, Chen; Gu, Xinyu; Shan, Dandan; Chu, Qingfei; Wang, Jing; Zhu, Haihong; Chen, Zhi (Frontiers in Cell and Developmental Biology, 2022)
Nonalcoholic fatty liver disease (NAFLD) is a class of metabolic-associated liver diseases. Aberrant lipid consumption plays an important role in NAFLD pathogenesis. It has been shown CD1d can bind to multiple different lysophospholipids and associated with NAFLD progression. However, the mechanism of CD1d regulation in NAFLD is not completely understood. In this study, we established a NAFLD mouse model by feeding C57/BL6J mice a high-fat diet (HFD) for 24 weeks. Subsequently, we performed integrated transcriptomics and metabolomics analyses to thoroughly probe the role of CD1d in NAFLD progression. In the present study, we demonstrate that CD1d expression was significantly decreased in our murine model of NAFLD. Additionally, we show CD1d knockdown (CD1d KO) in HFD-fed wild-type (WT) mice induced NAFLD, which resulted in weight gain, exaggerated liver injury, and hepatic steatosis. We uncover the crucial roles of CD1d deficiency results in accumulated lipid accumulation. We further explored the CD1d deficiency in NAFLD regarding the transcriptional landscapes, microbiota environment, metabolomics change, and transcriptomics differences. In conclusion, our data demonstrate CD1d plays an important role in NAFLD pathogenesis and may represent a potential therapeutic target for the further therapy.